Safety and efficacy of Lactobacillus reuteri NBF‐2 (DSM 32264) as a feed additive for cats. (11th January 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Lactobacillus reuteri NBF‐2 when used in feed for cats at a minimum dose of 6 × 10 9  colony forming units (CFU) per animal and day. The additive is a preparation of viable cells of L. reuteri DSM 32264. This species is considered by EFSA to be suitable for the qualified presumption of safety (QPS) approach establishing safety for the target species and the environment. The active agent fulfils the requirements of the QPS approach to the assessment of safety. Consequently, in the absence of concerns form other components of the additives, Lactobacillus reuteri NBF‐2 is presumed safe for the target animals and the environment. Lactobacillus reuteri NBF‐2 should be considered a potential respiratory sensitiser. In the absence of data, the FEEDAP Panel cannot conclude on the irritancy of the additive to skin and eyes or on its dermal sensitisation. The FEEDAP the Panel is not in the position to conclude on the efficacy of Lactobacillus reuteri NBF‐2 for cats.